Divorce: achieving social justice through clinical legal education - Du Plessis, M. A. (Faculty of Law, University of the Free State, 2008)
In achieving social justice, a law clinic has to strike a balance between teaching of students and service to its clients. Divorce, as a simple service case, proves to be a good learning vehicle for students, whilst affording their clients social justice. The different systems of marriage and divorce, both in the past and present, the different divorce courts and litigation methodology are discussed. Bearing this is mind, the question of whether universities are failing in educating students to become lawyers, is analysed and solutions are sought through clinical legal education, using the model of divorce proceedings.

Ten einde sosiale geregtigheid te bewerkstelling, moet 'n regskliniek 'n balans handhaaf tussen die opleiding van studente en dienslewering aan die kliente. Egskeiding, as 'n eenvoudige dienslewering, blyk 'n goeie leermiddel vir studente te wees, terwyl dit aan die kliente sosiale geregtigheid verseker. Die verskillende huweliksbede/ings en egskeidingsprosedures, beide in die verlede en tans, die verskillende egskeidingshowe en litigasiemetodes word bespreek. Gedagtig hieraan, word die vraag of universiteite faal in die opleiding van studente as juriste geanaliseer en oplossings word deur middel van kliniese regsopleiding gesoek, aan die hand van egskeidingsprosedures as model.
Keywords: Divorce; Social justice; Law clinic; Service to clients; Law students